Effects of resistance and strength training on serum phosphorus levels in male footballers: implications for physical educators and sports trainers - Mustafa, G.; Khan, W.; Arif, T.; Latif, H. (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Aim. Sports performance and overall health of athletes are highly dependent on various physiological markers. Among these, blood biochemistry is of great importance and should be carefully considered in athletes' training regimens. However, the effect of strength and resistance training on serum phosphorus levels still requires further clarification and more effective solutions. The aim of this study was to determine the effect of strength and resistance training on serum phosphorus levels in elite male soccer players.